An 8-step approach for the systematic development of an evidence-based exercise program for patients undergoing hematopoietic stem cell transplantation - An, Ki-Yong; Yu, Mi-Seong; Cho, Wonhee; Choi, Meeok; Courneya, Kerry S.; Cheong, June-Won; Jeon, Justin Y. (Frontiers in Oncology, 2023)
\Background: A tailored and reliable intervention program developed based on evidence is necessary for patients with serious health conditions. Objective: We describe the development of an exercise program for HSCT patients based on evidence from a systematic process. Methods: We developed the exercise program for HSCT patients using eight systematic steps: (1) a literature review, (2) understanding patient characteristics, (3) first expert group discussion, (4) development of the first draft of the exercise program, (5) a pre-test, (6) second expert group discussion, (7) a pilot randomized controlled trial (n=21), and (8) a focus group interview. Results: The developed exercise program was unsupervised and consisted of different exercises and intensities according to the patients’ hospital room and health condition. Participants were provided with instructions for the exercise program, exercise videos via smartphone, and prior education sessions. In the pilot trial, the adherence to the exercise program was only 44.7%, however, some changes in physical functioning and body composition favored the exercise group despite the small sample size. Conclusion: Strategies to improve adherence to this exercise program and larger sample sizes are needed to adequately test if the developed exercise program may help patients improve physical and hematologic recovery after HSCT. This study may help researchers develop a safe and effective evidence-based exercise program for their intervention studies. Moreover, the developed program may benefit the physical and hematological recovery in patients undergoing HSCT in larger trials, if exercise adherence is improved.